2014
DOI: 10.4315/0362-028x.jfp-14-183
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes and Listeria spp. Contamination Patterns in Retail Delicatessen Establishments in Three U.S. States

Abstract: Postprocessing contamination in processing plants has historically been a significant source of Listeria monocytogenes in ready-to-eat delicatessen meats, and therefore a major cause of human listeriosis cases and outbreaks. Recent risk assessments suggest that a majority of human listeriosis cases linked to consumption of contaminated deli meats may be due to L. monocytogenes contamination that occurs at the retail level. To better understand the ecology and transmission of Listeria spp. in retail delicatesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 20 publications
(21 reference statements)
2
43
1
Order By: Relevance
“…Here, we found that three sets of PFGE types that differed by three or fewer bands differed in the presence of an intact prophage regions; these findings clarified that a single L. monocytogenes clone presented by two PFGE types can persist in a deli. For example, we previously reported reisolation of two PFGE types (CU-11-320 and CU-8-96) in deli 2 (20); WGS showed that these two PFGE types represent one clone with a MRCA of Ͻ7 years.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Here, we found that three sets of PFGE types that differed by three or fewer bands differed in the presence of an intact prophage regions; these findings clarified that a single L. monocytogenes clone presented by two PFGE types can persist in a deli. For example, we previously reported reisolation of two PFGE types (CU-11-320 and CU-8-96) in deli 2 (20); WGS showed that these two PFGE types represent one clone with a MRCA of Ͻ7 years.…”
Section: Discussionmentioning
confidence: 97%
“…monocytogenes contamination at retail represents a complicated scenario with a mixture of persistence and repeated introduction from external sources. A key goal of the present study was to apply WGS-based subtyping to better understand the sources and transmission of L. monocytogenes in retail delis, building on a previous PFGE-based study of L. monocytogenes isolates obtained during a longitudinal study of 30 retail delis in three states (20). A specific goal was to use WGS-based subtyping to differentiate persistent L. monocytogenes contamination in delis from contamination that likely represents repeated introduction from an external source.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature also suggests that contamination at the retail level may be a significant cause of listeriosis (9)(10)(11). In both environments, L. monocytogenes has been isolated from food contact surfaces and non-food contact surfaces, such as floors and drains (12).…”
mentioning
confidence: 99%